2006
DOI: 10.1093/brain/awl196
|View full text |Cite
|
Sign up to set email alerts
|

Children with new-onset epilepsy: neuropsychological status and brain structure

Abstract: Abnormalities in cognition, academic performance and brain volumetrics have been reported in children with chronic epilepsy. The nature and degree to which these problems may be present at epilepsy onset or may instead become more evident over time remains to be determined. This study characterizes neuropsychological status, brain structure and their interrelationship in children with recent-onset epilepsy compared with healthy controls. Children (age: 8-18 years) with recent-onset idiopathic epilepsy (n = 53)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
182
3
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(210 citation statements)
references
References 67 publications
19
182
3
6
Order By: Relevance
“…Learning problems are common in school-aged children; however, they occur more often in children with uncomplicated epilepsy than in healthy peer controls. 9,[11][12][13] In fact, before diagnosis of epilepsy 11,28 or shortly thereafter, 9 children with uncomplicated epilepsy are already more likely to be receiving special education services compared with similar-aged controls. Before initiation of ASMs, adults with newly diagnosed seizures display evidence of relatively poorer memory function and processing speed compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning problems are common in school-aged children; however, they occur more often in children with uncomplicated epilepsy than in healthy peer controls. 9,[11][12][13] In fact, before diagnosis of epilepsy 11,28 or shortly thereafter, 9 children with uncomplicated epilepsy are already more likely to be receiving special education services compared with similar-aged controls. Before initiation of ASMs, adults with newly diagnosed seizures display evidence of relatively poorer memory function and processing speed compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In children with uncomplicated epilepsy, there is also ample evidence demonstrating an increased level of subtle cognitive as well as psychiatric and behavioral problems relative to healthy controls, which could also influence adult outcomes. [8][9][10][11][12][13] The respective impacts of seizure course versus learning and psychiatric problems on adult outcomes have not been distinguished. Understanding what places a child with epilepsy at risk for poorer outcomes in adulthood might contribute to management of childhood epilepsy, determining the need for early educational and psychiatric/psychological services, and planning pediatric to adult transition and transfer of care.…”
mentioning
confidence: 99%
“…A previous study in children with new-onset epilepsy found impairment in several cognitive domains, including intelligence, executive function, psychomotor speed, and language. 24 The reduction in cortical thickness in the frontal lobe could be related to impairment in executive function and psychomotor speed, and the reduced cortical thickness in the cingulate may reflect impairment in executive function.…”
Section: Discussionmentioning
confidence: 99%
“…Children with new-onset seizures or new-onset epilepsy are known to have neuropsychological deficits and academic underachievement, [23][24][25][26] even when they are intellectually healthy. It is possible that there is an antecedent neurobiologic alteration that predisposes to both seizures and neuropsychological deficits.…”
mentioning
confidence: 99%
See 1 more Smart Citation